PEMBELAJARAN BERPERSPEKTIF GENDER (Internalisasi Nilai-Nilai Gender dalam Pemberlajaran) - S, Samsinar (An - Nisa`, 2011)
This study discusses the gender perspective of learning. The target of this research is to understand the concept of gender and the internalization of gender in learning. This research method is qualitative. The results show that gender is a social construction that distinguishes the role and status of men and women in a society where the cultural background of social conditions. Gender is not universal, not the nature of women, and can not be changed because of the influence the course of history, changes in political, economic, social and cultural development and progress. Gender is the result of community formation. Learning the gender perspective is the learning that uses the concept of gender justice, equal partnership of harmony between men and women, pay attention to gender needs and interests. Therefore, to achiave gender equity in both the school environment, family, and society it is necessary to consciousness, sensitivity, and gender justice. Gender equality in learning requires involvement of all stalceholders including government, schools are institutions and especially its educators. Educators must become agents af change towards gender equality in learning through the learning process of gender sensitive so that he can internalize the values of gender in learning. And also required the standardization of textbooks are gender oriented.